STRATEGI KOMUNIKASI PEMBANGUNAN BUDAYA BANJAR “BAKISAH” DALAM PERSPEKTIF MEDIA DAN TEATER - Rafi'i, Akhyar; Rakhman, M. Fajrul; Hidayati, Dhea Galuh Ajeng (Journal of Gender Equality and Social Inclusion (gesi), 2024)
Bakisah culture, which originates from local culture in South Kalimantan Province by the Banjar tribe, is a storytelling tradition that is full of the meaning of life which is conveyed as a medium or performance in development communication. In its development, this culture was able to concretely transform into an adaptive and applicable communication strategy in presenting motivation through narratives of past stories with the aim of development. This research aims to analyze the communication strategies for developing Banjar Bakisah culture from a media and theater perspective. The research is an exploratory qualitative study with a phenomenological approach. Primary and secondary data collection through participant observation, in-depth interviews and literature study. Bakisah is interpreted as an instrument that has cultural values typical of the Banjar people, especially in the South Kalimantan area. In its implementation, this Bakisah culture becomes a medium for conveying development messages with the addition of sarcasm, jokes and short allusions. Likewise, in the implementation of the performance, humor becomes its own attraction to attract a wider audience. Until now, the use of storytelling culture as a medium and performance in development communication has not been optimal so it needs to be improved even more as a development communication strategy as well as an activity to preserve the local wisdom culture of the Banjar community.